AN OVERVIEW OF TRENDS IN THE REGULATION OF CLINICAL ETHICS COMMITTEES: AN OPINION FROM THE ITALIAN NATIONAL BIOETHICS COMMITTEE ARTICLE - Gianluca Montanari Vergallo (Cuadernos de Bioética, 2018)
In 2017, the Italian National Bioethics Committee (INBC) released an opinion paper titled “Clinical ethics committees”. Said document advocates for the creation of “clinical bioethics committees” in every suitable setting and lays out a set of guidelines aimed at regulating such committees’ functions. The recommendations deal primarily with the independence, requirements for counselling, structures, composition, tasks, placement, coordination, requisite competences, regulations. In the opinion’s contents there are: a) the need to entrust counselling and training on ethical issues within clinical practice to different committees than those that deal with ethical assessments of scientific trials and experimentation; b) the laying out of all the various functions and related competencies required of the ethics committees’ members; c) the necessity that all counselling practices be carried out by each committee as a whole, rather than by a single expert member; d) Committee’s independence. The authors elaborate on each one of the above mentioned aspects and highlight the importance of INBC’s recommendations in order to improve the quality standards of care delivered “to each patient’s bed”.